2007
DOI: 10.1021/es062544s
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Kraft Bleaching Effluent by Advanced Oxidation Processes Using Copper (II) as Electron Acceptor

Abstract: Two advanced oxidation processes (AOPs), TiO2/UV/O2 and TiO2/UV/Cu (II), were used to remove color from a Kraft bleaching effluent. The optimal decoloration rate was determined by multivariate analysis, obtaining a mathematical model to evaluate the effect among variables. TiO2 and Cu (II) concentrations and the reaction times were optimized. The experimental design resulted in a quadratic matrix of 30 experiments. Additionally, the pH influence on the color removal was determined by multivariate analysis. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…On the other hand, a 64% color removal was reported at pH = 7 for lignin decomposition, whereas a 99% was achieved at pH = 3 (Chang et al 2004). Correspondingly, Boroski et al (2008) and Rodrigues et al (2008) also reported the highest efficiency of this process at pH = 3 (Table 4), which was attributed to the positive charge that TiO 2 surface acquire in acid solutions, which favors the adsorption of anionic compounds to be prioritized resulting in a great decolorization of the effluent (Yeber et al 2007).…”
Section: Semi-conductor Photocatalytic Processesmentioning
confidence: 93%
See 4 more Smart Citations
“…On the other hand, a 64% color removal was reported at pH = 7 for lignin decomposition, whereas a 99% was achieved at pH = 3 (Chang et al 2004). Correspondingly, Boroski et al (2008) and Rodrigues et al (2008) also reported the highest efficiency of this process at pH = 3 (Table 4), which was attributed to the positive charge that TiO 2 surface acquire in acid solutions, which favors the adsorption of anionic compounds to be prioritized resulting in a great decolorization of the effluent (Yeber et al 2007).…”
Section: Semi-conductor Photocatalytic Processesmentioning
confidence: 93%
“…Biodegradation efficiency might also be improved using metallic ions as electron acceptors, as proposed by Yeber et al (2007) in the same essay the aeroxide treatment just described was also assessed. In short, it was confirmed that copper (II) efficiently acted as an electron acceptor when photocatalytic treatment was applied to an ECF bleaching pulp effluent to which this metallic ion was added.…”
Section: Uv/tio 2 /Cu (Ii)mentioning
confidence: 99%
See 3 more Smart Citations